Professional Exposure to Stress: The Risk of the Profession - Glomazić, Hajdana; Mikić, Andrijana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2022)
Caring for the mental health of professionals working with vulnerable groups, such as victims of violence and migrants, includes measures taken to monitor, protect and promote the well-being of people employed in these professions. It involves a system of different tools, practices and structures that have been developed to support the well-being of mental health professionals. The subject of this paper is the consideration of the relationship between professional exposure to stress and mental health. The aim of the work is to examine the experiences of professionals who provide psychosocial support to victims of violence and who are consequently professionally exposed to stress. The method used in the paper is a thematic, semi-structured interview. The results showed that chronic occupational exposure to stress affects mental health. This requires a well-designed organisational approach to the problem, including training and preparation of staff for trauma and stress at work, and providing supervisory support at work.